Effect of Behavior Modification on Outcome in Early- to Moderate-Stage Chronic Kidney Disease: A Cluster-Randomized Trial - 山縣 邦弘; Yamagata Kunihiro; Makino Hirofumi; Iseki Kunitoshi; Ito Sadayoshi; Kimura Kenjiro; Kusano Eiji; Shibata Takanori; Tomita Kimio; Narita Ichiei; Nishino Tomoya; Fujigaki Yoshihide; et al. (PLoS ONE, 2016)
Objectives\nOwing to recent changes in our understanding of the underlying cause of chronic kidney disease (CKD), the importance of lifestyle modification for preventing the progression of kidney dysfunction and complications has become obvious. In addition, effective cooperation between general physicians (GPs) and nephrologists is essential to ensure a better care system for CKD treatment. In this cluster-randomized study, we studied the effect of behavior modification on the outcome of early- to moderate-stage CKD.\n\nDesign\nStratified open cluster-randomized trial.\n\nSetting\nA total of 489 GPs belonging to 49 local medical associations (clusters) in Japan.\n\nParticipants\nA total of 2,379 patients (1,195 in group A (standard intervention) and 1,184 in group B (advanced intervention)) aged between 40 and 74 years, who had CKD and were under consultation with GPs.\n\nIntervention\nAll patients were managed in accordance with the current CKD guidelines. The group B clusters received three additional interventions: patients received both educational intervention for lifestyle modification and a CKD status letter, attempting to prevent their withdrawal from treatment, and the group B GPs received data sheets to facilitate reducing the gap between target and practice.\n\nMain outcome measure\nThe primary outcome measures were 1) the non-adherence rate of accepting continuous medical follow-up of the patients, 2) the collaboration rate between GPs and nephrologists, and 3) the progression of CKD.\n\nResults\nThe rate of discontinuous clinical visits was significantly lower in group B (16.2% in group A vs. 11.5% in group B, p = 0.01). Significantly higher referral and co-treatment rates were observed in group B (p<0.01). The average eGFR deterioration rate tended to be lower in group B (group A: 2.6±5.8 ml/min/1.73 m2/year, group B: 2.4±5.1 ml/min/1.73 m2/year, p = 0.07). A significant difference in eGFR deterioration rate was observed in subjects with Stage 3 CKD (group A: 2.4±5.9 ml/min/1.73 m2/year, group B: 1.9±4.4 ml/min/1.73 m2/year, p = 0.03).\n\nConclusion\nOur care system achieved behavior modification of CKD patients, namely, significantly lower discontinuous clinical visits, and behavior modification of both GPs and nephrologists, namely significantly higher referral and co-treatment rates, resulting in the retardation of CKD progression, especially in patients with proteinuric Stage 3 CKD.